Synthesis of PbTiO3 by use of polymeric precursors - Paris, E. C.; Leite, E. R.; Longo, Elson [UNESP]; Varela, José Arana [UNESP] (Elsevier, 1998)
Lead titanate powders were synthesized through the use of polymeric precursors according to the Pechini Process. The polymeric precursor was calcined at temperatures ranging from 300 to 600°C for 1 or 2 h. X-ray diffraction (XRD) showed that lead titanate crystallizes from the precursor at temperatures as low as 400°C. No intermediate carbonate phase was detected by Fourier transform infrared spectroscopy (FTIR) or by XRD. A powder with mean particle size of 150 nm was obtained after calcination of the precursor at 600°C for 1 h. © 1998 Elsevier Science B.V. All rights reserved.
Keywords: Lead titanate; Low temperature; PbTiO3; Pechini process; Polymeric precursor; Synthesis; Calcination; Crystallization; Ferroelectric materials; Fourier transform infrared spectroscopy; Powders; Synthesis (chemical); Thermal effects; X ray diffraction analysis; Polymeric precursors; Lead compounds